Unions Dues and Political Contributions – Great Britain, United States, Canada – A Comparison - Wanczycki, Jan (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1966)
This paper is concerned with court decisions and statutory enactments which had an effect on active participation of trade unions in political action and, in particular, how the Legislatures, and the courts in interpreting the relevant statutes, attempted to prevent or regularize the use of union dues, levies or funds for political purposes.